The Role of Graphic Design in Sustainable Marketing Amidst Digital Transformation: A Systematic Literature Review - Salsabila, Sabrina; Fhatih, Muhammad; Agustin, Mutiara; Mufid, Muhammad Kanda; Chairunnisa, Adelia (University of Science and Computer Technology, 2025)
The evolution of digital technology has significantly transformed marketing paradigms, emphasizing the importance of sustainability in business strategies. In this context, graphic design plays a critical role in conveying sustainability messages visually, resonating with increasingly environmentally conscious consumers. However, the fragmented understanding of graphic design's role in sustainable marketing within the broader ecosystem of digital transformation necessitates systematic exploration. This research aims to systematically evaluate the role of graphic design in supporting sustainable marketing strategies amidst digital transformation. Using a Systematic Literature Review (SLR) approach, the study analyzed 15 academic sources published between 2018 and 2024. The research focuses on identifying the most effective graphic design elements in communicating sustainability values, such as color schemes, typography, and eco-centric iconography, and their impact on consumer perceptions. The findings highlight that visual elements like green hues, minimalist typography, and nature-inspired icons significantly enhance brand equity and customer loyalty. Additionally, digital platforms, particularly social media, offer vast opportunities for disseminating visually impactful sustainability messages, fostering deeper consumer engagement. Despite these opportunities, challenges such as greenwashing and technological limitations remain critical barriers. The study concludes by proposing an integrated framework for leveraging graphic design to strengthen sustainable marketing strategies in the digital era. This research contributes to academic discourse by providing holistic insights into the intersection of graphic design, sustainability, and digital transformation. It also offers practical implications for businesses to enhance their communication strategies, ensuring authenticity and effectiveness in promoting sustainability values.